The role of activated sludge extracellular polymers and aerobic biomass in the removal of phosphorus from wastewater - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2006.